Pengentasan kemiskinan melalui pemberdayaan wirausaha dan program life skill untuk meningkatkan produktivitas kelompok UPPKS Kalipakem Baru - Bahri Bahri; Widodo Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This community service activity aims to increase the selling value of local products and the empowerment of entrepreneurs from members of the UPPKS Kalipakem Baru group. This activity focuses on improving life skills, productivity, marketing abilities, and online selling. The service activity delivery is done by the lecture method explaining the importance of making innovative products, improving life skills, the importance of marketing, and selling online. This activity provides training on how to create an online store and open discussions openly with participants. This activity expected that there would be an increase in the ability and expertise of participants in marketing and selling products online. This activity makes the product more known to the public and increases the number of orders so that the income of group members increases.